193k views
5 votes
Please help!! thanks!

Please help!! thanks!-example-1
User RandomEngy
by
5.6k points

1 Answer

3 votes

Answer:

A.) Yes

Explanation:

Plug in (3,2) into both equations ....

2(3) - 3(2) = 0

2(3) + 2 = 8

Then solve ....

2(3) - 3(2) = 0

6 - 6 = 0

0 = 0

2(3) + 2 = 8

6 + 2 = 8

8 = 8

Since both equation are true the solution (3,2) is true

User HandlerFive
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.